Ageing attenuates the effect of extracellular hyperosmolality on whole‐body heat exchange during exercise‐heat stress. (29th September 2020) - Meade, Robert D.; Notley, Sean R.; Rutherford, Maura M.; Boulay, Pierre; Kenny, Glen P.
Abstract : Key points: In humans, hypohydration attenuates sweat secretion and attenuates whole‐body heat loss, probably to mitigate further fluid losses and thereby support blood pressure regulation. Recently, however, we demonstrated that the hypohydration‐mediated reduction in net whole‐body heat exchange (evaporative heat loss – dry heat gain) was blunted in middle‐aged compared to younger men during moderate exercise in dry heat; albeit, the underpinning mechanisms could not be determined. Here we evaluated the hypothesis that those findings stemmed from a diminished influence of extracellular hyperosmolality on net whole‐body heat exchange in middle‐aged‐to‐older compared to young men. Consistent with that hypothesis, extracellular hyperosmolality induced by an intravenous infusion of hypertonic saline (3% NaCl) reduced net heat exchange and augmented rectal temperature to a greater extent in the young compared to middle‐aged‐to‐older men. Thus, age‐related differences in the influence of hypohydration on thermoregulatory function appear to be due to blunted sensitivity to hyperosmolality with ageing. Abstract: We recently demonstrated that sweating‐induced hypohydration attenuated whole‐body heat dissipation to a greater extent in young compared to middle‐aged men during exercise‐heat stress. Here, we evaluated whether this divergent response stemmed from an attenuated influence of extracellular hyperosmolality on heat exchange with ageing. To achieve this, ten young (mean (SD): 25 (5) years) and ten middle‐aged‐to‐older (61 (5) years) men completed two trials involving a 90‐min intravenous infusion of isosmotic saline (0.9% NaCl; ISO) or hyperosmotic saline (3.0% NaCl; HYP) followed by 60 min of cycling at a fixed metabolic heat production of 250 W/m 2 (∼50% peak aerobic power) in dry heat (40°C, ∼17% relative humidity). Whole‐body net heat exchange (evaporative heat loss – dry heat gain) was measured via direct calorimetry. Rectal temperature was monitored continuously. Heat exchange was attenuated in HYP compared to ISO in the young (233 (20) vs . 251 (17) W/m 2 ; P = 0.002) but not older group (229 (16) vs . 227 (20) W/m 2 ; P = 0.621). Further, heat exchange was lower in the middle‐aged‐to‐older vs . young men in ISO ( P = 0.034) but not in HYP ( P = 0.623). Similarly, end‐exercise rectal temperature was greater in HYP relative to ISO in the young (38.3 (0.4)°C vs . 37.9 (0.3)°C; P = 0.015) but not the middle‐aged‐to‐older men (38.3 (0.3)°C vs . 38.2 (0.2)°C; P = 0.652). Compared to the young, rectal temperature was greater in the middle‐aged‐to‐older during ISO ( P = 0.035) whereas no between‐group difference was observed in HYP ( P = 0.746). Our findings indicate that ageing blunts the effect of extracellular hyperosmolality on thermoregulatory function during exercise‐heat stress. Key points: In humans, hypohydration attenuates sweat secretion and attenuates whole‐body heat loss, probably to mitigate further fluid losses and thereby support blood pressure regulation. Recently, however, we demonstrated that the hypohydration‐mediated reduction in net whole‐body heat exchange (evaporative heat loss – dry heat gain) was blunted in middle‐aged compared to younger men during moderate exercise in dry heat; albeit, the underpinning mechanisms could not be determined. Here we evaluated the hypothesis that those findings stemmed from a diminished influence of extracellular hyperosmolality on net whole‐body heat exchange in middle‐aged‐to‐older compared to young men. Consistent with that hypothesis, extracellular hyperosmolality induced by an intravenous infusion of hypertonic saline (3% NaCl) reduced net heat exchange and augmented rectal temperature to a greater extent in the young compared to middle‐aged‐to‐older men. Thus, age‐related differences in the influence of hypohydration on thermoregulatory function appear to be due to blunted sensitivity to hyperosmolality with ageing.